Faktor-Faktor Risiko yang Berhubungan dengan Hipertensi di Kelurahan Belawan 1 - Diandra Kayladifa Rezha; Rapotan Hasibuan; Data Rizqueen Maipiana; Citra Mutiara Lubis; Charunnisyah Nurma Difhanny; Suci Yustrianti Marpaung (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Hypertension is also called the â€œsilent killerâ€ because people with hypertension often have no symptoms.Â  The National Institute of Heart, Lung and Blood in Indonesia estimates that half of people who suffer from hypertension are not aware of their condition.Â  The purpose of this study was to identify the factors associated with the onset of hypertension in the Belawan 1 Village area. This study used an analytical study with a case control approach.Â  The sample of this study was 236 respondents divided by a ratio of 1:1, namely 118 people in the control group and 118 people in the case group. The results of factor analysis of excessive salt consumption, lack of physical activity, family history of disease, consumption of excess fat, lack of fruits and vegetables, and excessive sugar consumption obtained pValue = 0.000, 0.016, 0.020, 0.040 0.042, 0.049 which means there is a relationship between physical activity factors, smoking habits, obesity and stress with the onset of hypertension.Â  Then the results of the risk factor analysis were retested using logistic regression to see which factors were the most influential among the independent variables with the incidence of hypertension, and the results obtained were excessive salt consumption, lack of physical activity, family history of disease, and lack of fruits and vegetables with AOR.Â  = 0.216, 0.389, 0.339, 0.459.Â  For this reason, it is recommended for health workers to provide counseling about hypertension, the causative factors and how to live a healthy and regular lifestyle so as to avoid hypertension.